2019
DOI: 10.3390/bs10010019
|View full text |Cite
|
Sign up to set email alerts
|

High School Dropout Rates of Japanese Youth in Residential Care: An Examination of Major Risk Factors

Abstract: Youths in Japanese residential care institutions often face challenges with social adaptation and career trajectories. This study aimed to examine the risk factors that lead residential care youths in Japan to drop out of high school. Eighty-nine residential care facilities completed a questionnaire that focused on the characteristics of residing high school students, their educational status, experiences of maltreatment before residence, diagnosed disabilities, and the timing of admission. A sample composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Similar concern has been expressed globally, with scholars in countries such as Australia (Pascoe et al, 2020), and India arguing for better initiatives to address the issue (Maheshwari et al, 2020). Such calls include increased support for marginalised groups at higher risk of dropout, such as young people from low socioeconomic backgrounds (McFarland et al, 2018), youth in institutional care (Ozawa & Hirata, 2020), young people of colour (Brown & Rodríguez, 2009), and neurodivergent or disabled youth (Plasman & Gottfried, 2018;Syvertsen et al, 2020).…”
Section: Global Education and The Crisis Of School Engagementmentioning
confidence: 88%
“…Similar concern has been expressed globally, with scholars in countries such as Australia (Pascoe et al, 2020), and India arguing for better initiatives to address the issue (Maheshwari et al, 2020). Such calls include increased support for marginalised groups at higher risk of dropout, such as young people from low socioeconomic backgrounds (McFarland et al, 2018), youth in institutional care (Ozawa & Hirata, 2020), young people of colour (Brown & Rodríguez, 2009), and neurodivergent or disabled youth (Plasman & Gottfried, 2018;Syvertsen et al, 2020).…”
Section: Global Education and The Crisis Of School Engagementmentioning
confidence: 88%
“…For instance, "behavioural engagement refers to students' active engagement (e.g., a student pays attention, participates, listens, and is involved in class activities"; McKellar et al, 2020, p. 2), which is considered to be essential to prevent dropout (Simons-Morton & Chen, 2009). Engagement is a significant predictor of dropout (Fall & Roberts, 2012;Ozawa & Hirata, 2020). Archambault et al (2009) verified that those students who reported low engagement from the beginning of high school presented higher risk of later dropout.…”
Section: Student Behavioral Engagement and School Dropoutmentioning
confidence: 99%
“…Engagement is a significant predictor of dropout (Fall & Roberts, 2012; Ozawa & Hirata, 2020). Archambault et al (2009) verified that those students who reported low engagement from the beginning of high school presented higher risk of later dropout.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…El compromiso del estudiante está relacionado con numerosos resultados académicos (Ayala y Manzano, 2018), incluidas las calificaciones de los estudiantes y la finalización de la escuela secundaria (Hershberger y Jones, 2018). En particular, se ha señalado que el compromiso es un predictor significativo de abandono escolar (Ozawa y Hirata, 2020). En este sentido, Archambault et al (2009) comprobaron que aquellos estudiantes con bajo compromiso desde el inicio de la educación secundaria presentaban mayores riesgos de abandono escolar posterior.…”
Section: Introductionunclassified